De novo centriole biogenesis during spermatogenesis in the model bryophyte Physcomitrium patens - Gomes Pereira, Sónia (2021)
"Centrioles play dual roles within Eukaryotic cells, being a key component of the main microtubule-organizing center of animal cells - the centrosome, and serving as basal bodies for cilia/flagella assembly. Due to their critical functions, centriole biogenesis is tightly regulated in time, space and number. In many eukaryotes, one centriole (daughter) assembles in close proximity to a pre-existing one (its mother), once per cell cycle. Such mechanism for centriole assembly is known as centriole duplication, and is thought to represent the ancestral pathway for centriole biogenesis. However, centrioles also assemble de novo in many cell types, tissues and species, with particular pathways and structures being employed to achieve such a goal. For example, in land plants with motile sperm cells, centrioles assemble de novo via two almost-exclusive structures: bicentrioles (e.g. bryophytes), or blepharoplasts (e.g. Ginkgo biloba). Nevertheless, and contrasting with centriole duplication, the mechanisms regulating de novo centriole biogenesis remain largely unknown. This is partially due to the lack of amenable model organisms and tools to tackle such processes. Still, this unexplored diversity is critical to understanding centrioles’ assembly, evolution and functions.(...)"